VIDEO FAIRY TALES AS A MEDIA FOR DISASTER MITIGATION IN PRIMARY SCHOOL AGE CHILDREN (GENDER EQUALITY: International Journal of Child and Gender Studies, 2021)
Every time a disaster occurs, one of the groups that becomes victims is children, both as victims of death and victims of injuries. Children who have survived a disaster are the group that suffers the most, they suffer the trauma of the disaster and a deep sense of loss. Therefore, disaster mitigation for children, especially primary school age children, is very important so that they are prepared to face the threat of disasters. The vast territory of Indonesia with a variety of disaster threats faced demands creative ideas so that disaster mitigation messages reach Indonesian children, one of which is the use of fairy tale videos. This study aims to find out the extent to which fairy tales can be used as a disaster mitigation media in developing the readiness of primary school children to face the threat of disaster. This research applies library research methods or literature review to the results of studies and relevant scientific publications. From this study, it shows that video media can significantly influence children's knowledge and attitudes. Disaster mitigation messages that are packaged in the form of fairy tale videos are able to attract the interest of children who are ultimately expected to build their preparedness in facing the threat of disaster.
Keywords: fairy tales; videos; elementary school age children; disaster preparedness